Entrepreneurship : Semerah Padi Enterprise / Nurhazwani Hamzah ... [et al.] - Hamzah, Nurhazwani; Azmi, Luqman Arif; Wam Alias, Wan Mohd Afiq; Ramli, Muhamad Hafizi; Wahab, Mohd Irwan (2009)
The objective of this business plan is to provide as a guideline for managing the proposed venture. In preparing this business plan, we has thought out and laid down the plans and strategies for running the venture. When the venture becomes a reality, the plans and strategies outlined in the business plan will be an important benchmark to help us gauge progress.